KONSEP EKOLOGI ISLAM SEYYED HOSSEIN NASR (STUDI KITAB AL-TAHARAH DALAM KAJIAN FIQH) - Masrokhin, - - (Irtifaq, 2014)
This research tries to reveal thebasic cause of enviromental crisisand the alternative solutionaccording to Seyyed Hossein Nasr.By summarizing his thoughts aboutthe connection between human andnature that tends to bemetaphysics, the writer tries todescribe the concept of Islamicecology in order to show the otherside of religion, especiallyIslam, that is nature-friendly.According to Nasr, humans have aworld-view that doesn’t think ofthe nature’s continuity because ofthe science desacralizationhappened in modern age. In suchway, nature will not be seen assomething to be exploitated forhuman’s needs anymore, but as anentity that humans will be able toreach a higher position with it.In islamic literature on fiqh,there is a chapter about altaharah.The lecturer of fiqh whohas mastered the methodological